2017
DOI: 10.1371/journal.ppat.1006427
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia elevates host methyltransferase expression to block an RNA virus early during infection

Abstract: Wolbachia pipientis is an intracellular endosymbiont known to confer host resistance against RNA viruses in insects. However, the causal mechanism underlying this antiviral defense remains poorly understood. To this end, we have established a robust arthropod model system to study the tripartite interaction involving Sindbis virus and Wolbachia strain wMel within its native host, Drosophila melanogaster. By leveraging the power of Drosophila genetics and a parallel, highly tractable D. melanogaster derived JW1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
121
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(138 citation statements)
references
References 56 publications
14
121
1
1
Order By: Relevance
“…Interestingly, the same pattern was not observed for DENV or WNV KUN . These data suggest that, for some viruses, the block hypothesized to occur early in infection, possibly at the virus translation stage [57][58][59], may be delayed if the initial virus population is large. A possible explanation is that a large starting population size allows the virus to partially overcome the initial challenge imposed by Wolbachia in these cells.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly, the same pattern was not observed for DENV or WNV KUN . These data suggest that, for some viruses, the block hypothesized to occur early in infection, possibly at the virus translation stage [57][58][59], may be delayed if the initial virus population is large. A possible explanation is that a large starting population size allows the virus to partially overcome the initial challenge imposed by Wolbachia in these cells.…”
Section: Discussionmentioning
confidence: 91%
“…A possible explanation is that a large starting population size allows the virus to partially overcome the initial challenge imposed by Wolbachia in these cells. However, subsequent cycles of infection may be hampered by low numbers of progeny viruses and the ability of Wolbachia to reduce the infectivity of these progeny [58,60], ultimately causing extinction of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Wolbachia-mediated suppression of viral replication in hosts is well described [7,8,11,12,64]. Multiple mechanisms may underlie this observation including interference with viral entry and very early stages of viral replication [38,53,57,[64][65][66][67][68][69][70][71]. All viruses depend on host translation machinery for replication of their genomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that these loci are not necessary for Wolbachia to inhibit Dengue virus in D. melanogaster (Rances et al, 2012;. Recently, Wolbachia mediated transcriptional changes at another locus was implicated in pathogen blocking; Wolbachia infection significantly upregulates the Drosophila melanogaster cytosinemethyltransferase gene Mt2, and reduction or ablation of Mt2 function (either by knockdown or knockout) diminishes Wolbachia's ability to inhibit virus replication (Bhattacharya et al, 2017). The mechanism by which Wolbachia achieves this upregulation, however, is not yet known.…”
Section: Wolbachia-induced Changes In Host Gene Expression Affect DIVmentioning
confidence: 99%